(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Low potato production in Ilaga District, Puncak Regency, Papua Province is caused by various factors, namely extreme environmental conditions, less optimal cultivation techniques, low seed quality, and poor soil fertility, so efforts to improve cultivation need to be made. This activity aimed to provide technical guidance and pilot demonstrations on cultivation, how to make organic fertilizers, seed propagation techniques, the introduction of pests, diseases, and their control. The technical guidance was carried out in Kago village, Ilaga District, on November 22-26, 2017. The location is located at an altitude of 2400 m above sea level. Farmers were given instructions on how to cultivate potatoes properly, how to get quality potato seeds on their land, how potato cultivation can be done in sacks when the climate is extreme, especially during the condition of frost and hail, fertilization techniques, and making organic fertilizers and recognizing pests and diseases in the field and their control with organic pesticides. Thirty-one potato farmers followed this activity. The participants showed enthusiasm for increasing potato production through appropriate cultivation. Monitoring of follow-up activities was carried out by extension workers of the local Agriculture Service. The result of the monitoring indicated that there had been improvements in cultivation techniques, organic fertilizer production, and quality potato seeds. Farmers have also recognized several types of pests and diseases and their biological control efforts. Based on the technical guidance, potato productivity increased to 3 tons /ha at the end of 2020. — Rendahnya produksi kentang di Distrik Ilaga, Kabupaten Puncak, Provinsi Papua disebabkan karena berbagai faktor, diantaranya kondisi lingkungan yang ekstrim (curah hujan tinggi, hujan dan embun es yang terjadi secara periodik, lama penyinaran matahari pendek pada bulan tertentu), teknik budidaya kurang optimal, kualitas bibit rendah, kesuburan tanah kurang, sehingga perbaikan teknik budidaya perlu dilakukan. Kegiatan ini bertujuan untuk memberikan bimbingan teknis (bimtek) dan demonstrasi plot (demplot) terkait dengan teknik budidaya, pembuatan pupuk organik, teknik perbanyakan benih, pengenalan hama dan penyakit serta teknik pengendaliannya. Kegiatan bimtek dan demplot dilaksanakan di kampung Kago, Distrik Ilaga pada tanggal 22-26 November 2017. Lokasi kegiatan terletak pada ketinggian 2400 m dari permukaan laut. Petani diberikan arahan tentang bagaimana membudidaya kentang dengan benar, bagaimana mendapatkan bibit kentang yang berkualitas di lahan mereka, bagaimana budidaya kentang dapat dilakukan di karung apabila iklim sangat ekstrim terutama ketika musim dingin yang menyebabkan terjadinya frost dan hail, teknik pemupukan dan pembuatan pupuk organik serta pengenalan hama-hama dan penyakit di lapang dan pengendaliannya dengan pestisida nabati. Hasil kegiatan diikuti oleh seluruh petani kentang yang berjumlah 31 orang. Para peserta menunjukkan antusias mereka untuk bagaimana meningkatkan produksi kentang melalui teknik budidaya yang sesuai. Monitoring kegiatan lanjutan budidaya dilaksanakan oleh penyuluh Dinas Pertanian setempat. Hasil dari monitoring ini menunjukkan adanya perbaikan teknik budidya, kemampuan petani dalam membuat pupuk organik, menghasilkan bibit kentang lebih berkualitas dan kemampuan petani mengenali beberapa jenis hama dan penyakit serta pengendaliannya secara alami, yang terindikasi dari meningkatnya produktiftas kentang menjadi 3 ton/ha pada akhir tahun 2020.